The financial determinants of the financial derivatives’ usage within SME businesses in Pakistan - Nawaz, Muhammad; Mohd Harif, Mohd Amy Azhar; Azhari, Adilah (Advances in Social Sciences Research Journal, 2018)
It had been acknowledged that the usage of financial derivatives improved the financial performance of the firms despite larger and smaller firms. Sufficient studies had been conducted on larger firms but there was a paucity of literature on financial derivatives’ usage within SMEs in the context of Pakistan. This gap created thirst for the current research in exploring the financial determinants of the financial derivatives’ usage within SMEs. This research was directed by pursuing the research problem: “how and why the financial determinants of the financial derivatives’ usage could be established within SMEs in Pakistan?” A qualitative research was conducted in order to explore this research issue. Respondents of this research were identified by applying snowballing sampling technique. Total twenty (20) convergent interviews were conducted to establish the literature and to confirm the financial determinants of the financial derivatives’ usage within SMEs. Thematic analysis technique was used to analyze the data. The outcomes of this research confirmed twelve (12) financial determinants of the financial derivatives’ usage, i.e. firm size, leverage, exchange rate exposure, interest rate exposure, liquidity, cash flow volatility, financial distress cost, reduction in taxes, firm value, agency cost, reduction in overall cost and un-invested cash. Two newly discovered financial determinants of the financial derivatives’ usage were reduction in cost and un-invested cash, which revealed the current research contribution to the existing body of knowledge. Moreover, this research provided theoretical, methodological, practical and policy implications. This research built a revised theoretical framework, which provided ground for future research.